Analisis Kepuasan Pelanggan Menggunakan Algoritma C5.0 - Dandi Junandi Purba; Muhammad Ridwan Lubis; Zulia Almaida Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Water is one of the necessities that are needed by living things, especially humans. In everyday life, humans cannot be separated from the need for air. PDAM is a regional-owned business unit, which is engaged in the distribution of clean water for the general public. However, along the way, along with receiving complaints from the public or customers, public complaints about the increasing difficulty of getting clean water are still an obstacle that can be completely overcome, for example in the North Sumatra area, precisely in Gunung Malela District. On the one hand, public demand will increase, but the quality of services provided is not comparable to meeting the demands of the community. Therefore, this study was conducted to determine customer satisfaction with PDAM Tirta Lihou in Gunung Malela District. Many branches of computer science study various algorithms, one of which is data mining methods, DSS, ANN, and others. This study uses a data mining method with the C5.0 algorithm to solve the problem of factors that affect customer satisfaction with PDAM Tirta Lihou, Gunung Malela District